Effect of Mathematical Literacy on Students' Learning Outcomes In The Subject of Systems of Linear Equations With Two Variables - Okviani Syafti; Sefrinal; Baik Pratama (Cv. Kilau Rashdan Publishing, 2026)
This study aims to determine the effect of mathematical literacy on students' learning outcomes in the topic of Systems of Linear Equations in Two Variables (SPLDV). This research employed a quantitative approach using correlational and simple linear regression methods. The sample consisted of 26 eighth-grade students of the Unggul class at SMPN 1 Linggo Sari Baganti. Mathematical literacy data were collected through questionnaires, while learning outcomes were obtained from SPLDV tests. The results showed a moderate positive correlation between mathematical literacy and learning outcomes with a correlation coefficient of 0.52. Regression analysis indicated a significance value of 0.007 < 0.05, meaning that mathematical literacy has a significant effect on students' learning outcomes. Therefore, higher mathematical literacy contributes to better learning outcomes.